Women and Alcohol in Gothenburg (WAG) - WAG - Interviews 1994-1998 - Hensing, Gunnel; Spak, Fredrik (University of Gothenburg, 2014)
The study Women and Alcohol in Gothenburg (WAG) is a longitudinal study that started in 1986.
WAG has data from three interview waves, 1989-1992, 1994-1998 and 2000-2002. It comprises data from 2421 interviews, including 1432 baseline interviews and 989 follow-up interviews.

In 2013 a new data collection has started in the project.

WAG is designed as a two stage study. In the first step, specific female birth cohorts included in the study population for the first time and registered in central and western districts of Gothenburg, received a 13-item alcohol problem screening questionnaire called Women Screening and Alcohol (SWAG). In the second step, women were selected for a structured interview by stratified sampling according to their scores in the SWAG questionnaire. This two-step way enables the group of women with alcohol problems to be greater than in a random sampling.
Each wave of data collection consist of baseline interviews birth cohorts included for the first time, as well as follow-up interviews with earlier baseline cohorts.

The structured interview questionnaire mainly comprises issues of alcohol habits and mental health, including psychiatric disorders. The questionnaire further covers topics such as women’s working life and family situation, socioeconomic background factors, legal and illegal drug use, past experience from childhood and adolescence and sexual abuse and physical violence during child- and adulthood. Psychiatric diagnoses have been established by clinician interviewers according to the International Classification of Disease (ICD), DSM-III-R and DSM-IV. In the third data collection between 2000 and 2002, the instrument called International Neuropsychiatric Interview (M.I.N.I) was included in the questionnaire and used for diagnostic purpose.

Purpose:

The primary aim of the project is to follow the development of drinking habits and alcohol problems, to examine the motives women have to drink alcohol, to study the negative consequences of alcohol and to study the relationship between alcohol problems, mental health disorders, anxiety and depression.

Data collection between 1994-1998 consist of baseline interviews with birth cohorts included for the first time, as well as follow-up interviews with earlier baseline cohorts.

WAG är en förkortning av projektets engelska namn ”Women and alcohol in Gothenburg”, som på svenska översätts till ”Kvinnor och alkohol i Göteborg”. Studien är longitudinell och startade år 1986. Data har samlats in under åren 1989-1992, 1994-1998 och 2000-2002. Från dessa tre insamlingsperioder finns data från 2421 intervjuer, omfattande 1432 baslinjeintervjuer och 989 uppföljningsintervjuer.

Under 2013 påbörjades en ny datainsamling i studien, som är pågående.

Studien är upplagd som en så kallad tvåstegsstudie. I det första steget skickas ett screeningformulär, SWAG (Screening, women and alcohol in Göteborg), ut till samtliga kvinnor födda ett visst årtal och som är bosatta inom en viss del av Göteborg. Med hjälp av screeninginstrumentet kunde man identifiera personer med alkoholproblem. I andra steget valdes sedan kvinnor ut för en strukturerad intervju via stratifierat urval, baserat på hur de svarat i frågeformuläret. Detta sätt har man använt för att få en större grupp kvinnor med alkoholproblem än vad som hade varit möjligt med ett vanligt slumpmässigt urval.

Varje omgång av datainsamling inkluderar dels uppföljningsintervjuer med tidigare baslinjekohorter, och dels baslinjeintervju med födelsekohorter som inkluderas för första gången.


De strukturerade intervjuformulären inkluderar framför allt frågor om alkoholvanor och psykisk hälsa, inklusive psykiska sjukdomar. Enkäten omfattar även frågor kring kvinnors arbetsliv och familjesituation, socioekonomiska bakgrundsfaktorer, droganvändning, tidigare erfarenheter från barndomen och tonåren, samt sexuella övergrepp och fysiskt våld under barn- och vuxenlivet.

Psykiatriska diagnoser har fastställts enligt internationell klassificering av sjukdomar (ICD), DSM-III-R och DSM-IV. I den tredje datainsamling, mellan 2000 och 2002, användes instrumentet som kallas International Neuropsychiatric Interview (MINI) för diagnostiska ändamål.

Syfte:

Det huvudsakliga syftet med WAG är att följa utvecklingen av alkoholvanor och alkoholproblem, att undersöka vilka motiv kvinnor har för att dricka alkohol, att studera negativa konsekvenser av alkoholen och att studera sambanden mellan alkoholproblem, psykiska sjukdomar, särskild ångest och depression.

Vid den andra datainsamlingen, 1994-1998, genomfördes dels uppföljande intervjuer med tidigare deltagare, och dels baslinjemätning med ny kohort kvinnor.
WAG - Kvinnor och alkohol i Göteborg - WAG - Intervjuer 1994-1998
Keywords: Health Services; Hälso- och sjukvård; Cohort Studies; Kohortstudier; Psychiatry; Psykiatri; Life Style; Livsstil; Longitudinal Studies; Longitudinella studier; Prospective Studies; Prospektiva studier; Population Surveillance; Populationsövervakning; Socioeconomic Factors; Socioekonomiska faktorer; Risk Factors; Riskfaktorer; Women's Health; Kvinnohälsa; Women; Kvinnor; Alcoholism; Alkoholism; Alcohol Drinking; Alkoholkonsumtion; Alcohol-Related Disorders; Alkoholmissbruk; Family; Familj; Public Health; Folkhälsa; Leisure Activities; Fritidsaktiviteter; Health; Hälsa; Substance-Related Disorders; Missbruksrelaterade sjukdomar; Depression; Depression; Interpersonal Relations; Mellanmänskliga relationer; Mental Health; Psykisk hälsa; Mass Screening; Massundersökning; Sick Leave; Sjukfrånvaro; Suicidal Ideation; Självmordstankar; Self Concept; Självuppfattning; Social Conditions; Sociala villkor; Social Class; Samhällsklass; Occupational Exposure; Yrkesmässig exponering; epidemiology; epidemiologi; mental illness; psykisk ohälsa; HEALTH; HÄLSA; Medical and Health Sciences; Medicin och hälsovetenskap; Health Sciences; Hälsovetenskap; Public Health, Global Health and Social Medicine; Folkhälsovetenskap, global hälsa och socialmedicin